Basic Colors in Javanese and Indonesian Languages: Natural Semantic Metalanguage Theory - Ningrum, Dwi Kurnia Surya; Brahmana, Christanta Rejuna Phanes S; Mulyadi, Mulyadi (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2024)
This study explores the variety of basic colors in the Javanese language and aims to elucidate their meanings using the Natural Semantic Metalanguage Theory. Employing a qualitative research paradigm, data were collected from various sources, including Indonesian and Javanese dictionaries, LCC Indonesian 2022 and LCC Javanese corpus from CQPWeb. The study identifies 10 basic colors in Javanese, namely Ireng (black), Putih (white), Abang (red), Ijo (green), Kuning (yellow), Biru (blue), Soklat (brown), Wungu (purple), Jambon (pink), and Klawu (gray), while Indonesian has only six basic colors: Hitam (black), Putih (white), Merah (red), Kuning (yellow), Hijau (green), and Biru (blue). Utilizing the features of the Natural Semantic Metalanguage (NSM) theory and the Basic Color Term approach by Berlin and Kay, the study analyzes the Javanese colors. The research highlights differences in color explications between Javanese and Indonesian, stemming from variances in using semantic atoms to explain color meanings. For instance, in Javanese, the color black is explicated using a spice herb named